Chemical recycling of brominated flame retarded plastics from e-waste for clean fuels production: A review. (August 2016) - Ma, Chuan; Yu, Jie; Wang, Ben; Song, Zijian; Xiang, Jun; Hu, Song; Su, Sheng; Sun, Lushi
Abstract: Electronic waste plastics (e-waste plastics) have been one of the emerging and fastest-growing waste streams due to the increasing number of generation in waste electrical and electronic equipment (WEEE). Given that brominated flame retardant (BFR) materials in e-waste plastics have been the major impediment for recycling treatment, chemical recycling has been proposed as an environmentally friendly method of recycling e-waste plastics for clean fuels production or chemical feedstocks. This paper summarized the current techniques of BFR-plastics recycling with a view to solving energy crisis and the environmental degradation of BFR-plastics. Emphasis was paid on the recent chemical treatment of BFR-plastics, including pyrolysis, co-pyrolysis and catalytic cracking, which are yet to be completely feasible in conversion of BFR-plastics for clean fuels production. Hydrothermal treatment is regarded as a novel high-efficiency technology to recycle BFR-plastics, which can be a potential process for the in situ debromination of oil products. An advanced chemical recycling technique, pyrolysis-catalytic upgrading process, is highlighted. The recycling route of pyrolyzing BFR-plastics prior to catalytic upgrading was intended to obtain high quantity oils, and then the upgrading process of pyrolysis oils was conducted by means of catalytic hydrodebromination with the aim of obtaining bromine-free oils for commercial applications. In short, the integration of pyrolysis with catalytic upgrading process can provide significant economic and environmental options in conversion of e-waste plastics into useful and high-value materials. Further investigations are required to develop the pyrolysis-catalytic upgrading process to become sustainable and commercially viable for clean fuels production.